2023
DOI: 10.3389/fpls.2023.1122218
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and plant defense elicitation activities of Eucalyptus oil decrease the severity of infections by Xylella fastidiosa on almond plants

Abstract: The activity of Eucalyptus essential oil against eleven strains pertaining to six species of plant pathogenic bacteria was studied using growth inhibition and contact assays. All strains were susceptible to the formulation EGL2, and Xylella fastidiosa subspecies and Xanthomonas fragariae were the most sensitive. The bactericidal effect was strong causing 4.5 to 6.0 log reductions in survival in 30 min at concentrations in the range of 0.75 to 15.0 μl/ml depending on the bacteria tested. Transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The study found that all phytopathogenic bacteria were susceptible to the oil, with Xf and Xanthomonas fragariae being the most affected. The bactericidal effect was particularly strong, with a lytic effect observed in three subspecies of Xf used in the study [111].…”
Section: Use Of Products That Affect the Development Of The Bacteriamentioning
confidence: 84%
“…The study found that all phytopathogenic bacteria were susceptible to the oil, with Xf and Xanthomonas fragariae being the most affected. The bactericidal effect was particularly strong, with a lytic effect observed in three subspecies of Xf used in the study [111].…”
Section: Use Of Products That Affect the Development Of The Bacteriamentioning
confidence: 84%
“…(2011) (MIC 500 µL/L). Montesinos et al. (2023) reported a reduced susceptibility of Xap (MIC 10 – 30 µl/mL) and other species such as X. fragariae and X. axonopodis pv.…”
Section: Discussionmentioning
confidence: 99%
“…The Xap isolates tested in this study (Xap3, XapG2) showed higher sensitivity (with MIC values of 125 and 250 µg/mL) to lemon grass EO than the Xap strain examined by Zhao et al (2011) (MIC 500 µL/L). Montesinos et al (2023) reported a reduced susceptibility of Xap (MIC 10 -30 µl/mL) and other species such as X. fragariae and X. axonopodis pv. vesicatoria (MIC < 5 and 10 -30 µl/mL, respectively) to eucalyptus EO, as compared to our observations, however they used a different method, the agar HPTLC chromatograms with retardation factor (hR F ) scale of thyme (T), cinnamon (CN), clove (CL), tea tree (TT), rosemary (R), eucalyptus (EU), lemon grass (LG), lemon balm (LB1 from Primavera, LB2 from Olivia Naturals), and citronella grass (CG) essential oils, and thymol (t), transcinnamaldehyde (c), eugenol (e), citral (ci: neral+geranial), and citronellal (cl) standards after derivatization with vanillin-sulphuric acid reagent (A, D, G), and bioautograms using Xanthomonas arboricola pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation